"They're always wrong anyway": exploring differences of credibility, attraction, and behavioral intentions in professional, amateur, and robotic-delivered weather forecasts. Issue 1 (1st January 2021) - Spence, Patric R.; Edwards, Chad; Edwards, Autumn; Rainear, Adam; Jin, Xianlin
ABSTRACT: Weather-related communication lends itself well to various styles of delivery and medium. Yet, new communication technologies have changed information consumption in this domain and created changes for broadcast media. Some new media platforms allow the participation of nonprofessional (amateur) agents, whereas others, such as social robotics or chatbots, allow for the removal of a human-element entirely. As these platforms further proliferate in society, it is vital to understand individuals' perceptions about both the content and the medium, especially in messages which can ultimately remove an individual from danger such as those about weather risks. This experimental study examines differences when individuals view a video/broadcast weather forecast delivered by a professional, an amateur, or a social robot. Results suggest that individuals find professional meteorologists significantly more credible than amateur or robotic counterparts.